Analisis Surat Al-Anfāl Ayat 17: Upaya Mengungkap Sisi Transendental Hermeneutika Double Movement - Miatul Qudsia; Muhammad Faishal Haq (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2021)
The study of the Koran from a contextual point of view continues to grow. One of the offers that has been continuously studied and applied is the double movement theory initiated by Fazlur Rahman and developed by Abdullah Saeed. The double movement theory emphasizes the socio-historical context of the Koran and the present. To bridge the two periods, a researcher must sensitively take the meaning of the verse being studied or what is called the moral ideal. Thus, the meaning of the purpose of the revelation of the Qur'anic verse will continue to be conveyed at any time. The object of the application of the double movement is indeed law verses, so as to produce a moral ideal that is real or concrete. However, in this study, the researcher found that double movement not only produces concrete moral ideals, but also transcendental ones. The verse studied is the verse of war, surah al-Anfāl verse 17. So that, the result is that the moral ideal which is concrete from this verse is that it is permissible and even required to take the path of war if it is in an emergency and is depressed. For example, there is pressure, discrimination and so on that cause torture. And, the transcendental moral ideal is that there must be an attitude of tawakal and endeavor from every Muslim. That Allah can make real what is considered impossible by humans.